Cephalometric Norms in an Omani Adult Population of Arab Descent - Al-Busaidi , Ibrahim; Govinakovi , Prashantha S; Senguttuvan , Viswapurna (Sultan Qaboos University medical journal, 2018)
: Objectives: This study aimed to establish cephalometric norms for an Omani population of Arab descent and to compare these with established cephalometric values for Caucasians. Methods: This cross-sectional study was conducted at the Military Dental Centre and Oman Dental College in Muscat, Oman, between May 2014 and October 2016. A total of 150 Omani patients between 20–29 years old seeking orthodontic treatment were included. All participants had a symmetrical face, class I molar and canine relationships, proper intercuspation, a normal overjet/overbite (<3 mm) and mild spacing/crowding of the teeth (≤3 mm). Lateral cephalography was performed in centric occlusion with the lips relaxed and the head in a natural position. Cephalometric measurements were then compared with Eastman Standard norms. Results: The Omani subjects were found to have a slightly retrusive maxilla, an increased angle between the maxillary and mandibular planes and shorter facial heights in comparison to the Eastman Standard norms. Furthermore, incisor relations were edge-to-edge in nature and the interincisal angle was reduced, suggesting that the Omani subjects had more proclined incisors. In addition, the lips were more protrusive and the nasolabial angle was more obtuse. Conclusion: In the Omani sample, increased proclination of the incisors was observed in comparison to Eastman Standard norms. As such, slightly more proclined incisors should be considered acceptable and natural among Omani patients of Arab descent. The cephalometric findings of this study may be helpful in the diagnosis and treatment planning of orthodontic problems among Omanis of Arab descent.